Halal Tourism - The Type of Tourism Required in Azerbaijan - ALIYEV, Vasif (Journal of Environmental Management and Tourism, 2021)
Purpose - This number of tourists in Azerbaijan has been growing in recent years due to the increase in tourism revenues, visa convenience, fight against terrorism, and political stability. To further increase this growth, turning to Halal tourism may be the solution. One of the aims of this study is to raise awareness among the Azerbaijani tourism stakeholders about the basic needs of the growing Halal tourism market in the world and at the same time to share information about the sector. Azerbaijan is one of the most important actors in the Halal tourism market with its historical heritage and developing tourist infrastructure. This study includes examining the current potential of halal concept hotel establishments in Azerbaijan. Design/methodology/approach - Descriptive statistics method was used in the study. For this purpose, the conceptual framework of Halal tourism has been identified by conducting a detailed literature review on the subject, and the in-depth literature studies have been reinforced with statistical data. Findings - In this study, statistics of the number of Muslim and non-Muslim tourists entering the country between the years 2015-2020 are presented, and the GDP of Arab countries and tourism expenditures are shown. Originality/value - As a result of the research, the most important points that halal concept hotels should pay attention are determined to be providing guests with adequate worship facilities, ensuring halal standards in food and beverage services and designing hotel activities in accordance with Islamic principles.